A Cross-Border Digital Financial Management: A Systematic Literature Review - M.Khairul Anwari; Maria Christina Iman Kalis; M. Irfani Hendri (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The development of digital governance has accelerated the transformation of public financial management through e-budgeting, e-reporting, and integrated digital financial systems. However, studies discussing digital public financial management in cross-border areas remain fragmented and dispersed across disciplines. This study aims to systematically map the development of research on digital public financial management in cross-border contexts through publication trends, influential journals, active researchers, keyword patterns, countries, institutions, and research areas. This research employed a qualitative approach using a Systematic Literature Review (SLR) and bibliometric analysis based on 48 Scopus-indexed articles published between 2020 and 2026. The findings indicate that publications increased significantly after 2023, reflecting growing scholarly interest in cross-border digital finance and governance. The literature is dominated by economics and finance perspectives, while public financial governance and fiscal accountability in border areas remain underexplored. In addition, knowledge production is still concentrated in a limited number of countries and institutions, particularly in Europe. This study contributes by providing an intellectual mapping of the field and identifying opportunities for future research integrating digital governance, public financial management, and border studies.